Progression of immunoglobulin A nephropathy (IgAN) in a Hispanic/Latinx population in the United States - Sim, John J.; Cannizzaro, Nancy T.; Chen, Qiaoling; Nunna, Sasikiran; Mathur, Mohit; Pinto, Cibele (Frontiers in Nephrology, 2026)
BackgroundImmunoglobulin A nephropathy (IgAN) is a leading cause of chronic kidney disease (CKD) worldwide. While racial and ethnic differences in disease progression are well documented, the Hispanic/Latinx populations remain understudied despite their elevated risk of kidney failure among other CKD populations.ObjectiveThis study aimed to evaluate the kidney function decline and progression in Hispanic/Latinx patients with biopsy-proven IgAN within a large, integrated healthcare system and to contextualize to other racial/ethnic groups.MethodsWe conducted a retrospective case series study of 259 Hispanic/Latinx adults with biopsy-proven IgAN from the Kaiser Permanente Southern California (KPSC) health system. Patients were followed from biopsy to ≥50% decline in the estimated glomerular filtration rate (eGFR), kidney failure, mortality, the study end date of November 30, 2022, or disenrollment. Annualized eGFR decline and the incidence of composite kidney outcomes were assessed.ResultsAt diagnosis, Hispanic/Latinx patients had significant CKD and a high risk of progression to kidney failure, indicated by a median eGFR of 56 ml min−1 1.73 m−2 and a median urine protein/creatinine ratio of 1.8 g/g. Common treatments included immunosuppressive agents (41%), angiotensin-converting enzyme (ACE) inhibitors (48%), and angiotensin receptor blockers (ARBs; 20%). The mean annual eGFR decline was −4.5 ml min−1 1.73 m−2, and 30.9% experienced rapid decline (>5 ml min−1 1.73 m−2 per year). The composite kidney outcome occurred at 73.3 events per 1,000 patient-years, with a median time to event of 2.8 years and a median age at event of 46 years.ConclusionHispanic/Latinx patients with IgAN demonstrate rapid kidney function decline and early-onset kidney failure. These findings underscore the need for earlier detection and targeted management in this underserved group.